Persönlichkeit der Fussballer AMP Futbol = Personality footballers AMP Futbol - Kalinowski, Paweł; Lischka Ołpińska, Marta (Journal of Education, Health and Sport, 2016)
Kalinowski, Paweł, Lischka Ołpińska, Marta . Persönlichkeit der Fussballer AMP Futbol = Personality footballers AMP Futbol. Journal of Education, Health and Sport. 2016;6(8):227-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60260 http://ojs.ukw.edu.pl/index.php/johs/article/view/3751 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016. QUALITY IN SPORT 3 (2) 2016, s. 65-72, e-ISSN 2450-3118 Praca wpłynęła do redakcji 13 III 2016, praca została przyjęta do druku 23 VI 2016 DOI: http://dx.doi.org/10.5281/zenodo.57217 PBN: https://pbn.nauka.gov.pl/sedno-webapp/works/735282 Paweł Kalinowski[1], Marta Lischka Ołpińska Doktoranden AWF Poznań Persönlichkeit der Fussballer AMP Futbol Personality footballers AMP Futbol Zusammenfassung Die Persönlichkeitsmerkmale sind Variablen, die signifikant mit körperlichen Aktivitäten verbunden sind. Zur Zeit bezieht sich die Mehrheit von Studien auf die Persönlichkeitsbetrachtung; daher werden ausgewählte Konstrukte dieser Betrachtung im Folgenden kurz dargestellt. Oft müssen behinderte Menschen zusätzlich mit sich selber kämpfen. Es ist wahrscheinlich, dass ausgewählte Persönlichkeitsmerkmale dies beeinflussen. Ziel der vorliegenden Studie ist die Einschätzung der Gewichtung von Persönlichkeitsmerkmalen im Sinne des Fünf-Faktoren-Persönlichkeitsinventars bei behinderten Sportlern. Die Überprüfung wurde durch einen Vergleich (Normstichprobe) von gesunden und behinderten Sportlern durchgeführt. An der Studie beteiligten sich insgesamt 16 Sportler mit einseitigen Amputationen von Extremitäten. Zum Einsatz kam ein Fragebogen Fünf-Faktoren-Modell. Die Studie wurde im März 2015 durchgeführt. Schlüsselbegriffe: Persönlichkeit, Amp Futbol, Sport von behinderten Menschen Fußball. Summary Personality traits are the variables significantly related to the functioning of sporting activities. Today, most research in sport refers to the trait approach to personality. Hence, in the first place, selected constructs in this field will be briefly characterized. It is often the case that people with disabilities have to fight with themselves. Perhaps, selected personality traits might be of an influence. The aim of this study was to compare the level of personality traits of athletes with disabilities with the average value in the normative group. The study was conducted on a group of 16 players representing the team of unilateral amputee footballers. The study was conducted using a personality questionnaire NEO-FFI in the month of March 2015. Keywords: Personality, AMP football, Sports persons with disabilities, Football. [1]mgr Paweł Kalinowski e-mail: pawel.kalinowski@gmail.com, mgr Marta Lischka Ołpińska